Resource capture and productivity of agroforestry systems in Kenya - Howard, Stephen B. (1997)
Resource capture and utilisation were studied in two agroforestry systems at the International Centre for Research in Agroforestry (ICRAF) Research Station at Machakos, Kenya. The agroforestry systems examined contained two contrasting tree species, leucaena (Leucaena leucocephala (Lam.) de wit) and grevillea (Grevillea robusta), and the C3 and C4 crops, cowpea (Vigna unguiculata) and maize (Zea mays, Katumani composite).